New Weak Keys with Parity Patterns in the RC4 Stream Cipher - Evaristo José Madarro-Capó; Carlos Miguel Legón-Pérez; Guillermo Sosa-Gómez; Omar Rojas (Cryptography, 2024)
The RC4 cryptographic algorithm is the most extensively studied stream cipher of the past two decades. This extensive research has resulted in numerous publications, many of which identify various vulnerabilities. Although these vulnerabilities do not preclude the correct use of the algorithm, they complicate its practical implementation. In this paper, we present a novel weakness in the RC4 cipher. Our findings indicate that, for input keys exhibiting certain patterns, the parity of the values in the output permutation of the KSA can be determined with high probability from the parity of its position in the output permutation. Furthermore, the use of keys with these specific patterns leads to noticeable distortions in several bytes of the RC4 output.